2011
DOI: 10.1107/s1744309110051298
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary joint neutron time-of-flight and X-ray crystallographic study of human ABO(H) blood group A glycosyltransferase

Abstract: The biosyntheses of oligosaccharides and glycoconjugates are conducted by glycosyltransferases. These extraordinarily diverse and widespread enzymes catalyze the formation of glycosidic bonds through the transfer of a monosaccharide from a donor molecule to an acceptor molecule, with the stereochemistry about the anomeric carbon being either inverted or retained. Human ABO(H) blood group A α‐1,3‐N‐acetylgalactosaminyltransferase (GTA) generates the corresponding antigen by the transfer of N‐acetylgalactosamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…With the exception of the GTA neutron diffraction studies [44] hydrogen atoms are not directly observed, so distances are given between centers of non-hydrogen atoms. Italic enzyme names indicate the model did not contain an acceptor molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the GTA neutron diffraction studies [44] hydrogen atoms are not directly observed, so distances are given between centers of non-hydrogen atoms. Italic enzyme names indicate the model did not contain an acceptor molecule.…”
Section: Resultsmentioning
confidence: 99%
“…A neutron structure of the human retaining enzyme GTA at LANCE PCS (PDB 4DHH associated with [44]) has been reported. More detailed analysis of this structure has revealed an aprotic active site that appears to be incompatible with a dissociative mechanism.…”
Section: Introductionmentioning
confidence: 99%